Analysis of total ozone, potential vorticity and tropopause pressure over southeast Asia during winter - BEGUM, D. A. (MAUSAM, 1996)
This article shows the analysis of total ozone and potential vorticity and also tropopause pressure during winter period (December, January and February) over the area 20°-50°N, 90°.160oE (southeast Asia), This is done for three different latitude bands 20o-30oN, 30° -40° N and 40°S -50oN. Due to maximum, latitudinal gradient of ozone in the lower latitudinal band, high correlation is found with potential vorticity and also with tropopause level